Rational Use of Ceftriaxone in Necrotizing Fasciitis and Mortality Associated with Bloodstream Infection and Hemorrhagic Bullous Lesions - Hung-Yen Chen; Tsung-Yu Huang; Jiun-Liang Chen; Liang-Tseng Kuo; Kuo-Chin Huang; Yao-Hung Tsai (MDPI AG, 2022)
Necrotizing fasciitis (NF) is an uncommon life-threatening necrotizing skin and soft tissue infection. The formation of hemorrhagic bullae is a special skin sign of NF. The purposes of this study were to investigate the incidence of hemorrhagic bullae formation and bacteremia associated with different organisms, to appraise the appropriate use of ceftriaxone, and to compare the clinical and laboratory risk indicators of NF patients with Gram-positive and Gram-negative infections on the initial examination. Methods: From March 2018 to December 2020, there were seventy-four NF patients with positive monomicrobial bacterial cultures enrolled based on surgical confirmation, and were categorized into two groups: the Gram-positive group and the Gram-negative group. Ceftriaxone susceptibility tests were carried out using the standard disk diffusion technique. Data, such as demographics, clinical outcomes, microbiological results, presentations of hemorrhagic bullae, and laboratory findings, were compared among these two groups. Results: The Gram-negative group included 52 patients, of whom 6 patients died, resulting in a mortality rate of 11.5%. The Gram-positive group included 22 patients and none died. Patients with bacteremia, hemorrhagic bullae, shock, fever, higher segmented forms and banded forms, and lower platelet counts constituted higher proportions in the Gram-negative group than in the Gram-positive group. The multivariate analysis identified six variables for the differentiation of Gram-negative and Gram-positive NF: the presentation of bacteremia, hemorrhagic bullae, shock at first consultation, fever with body temperature > 38.5 °C, band forms > 0%, and segmented forms ≦ 74%. A total of 66 isolates (89.2%) was susceptible to ceftriaxone. Conclusions: Gram-negative NF patients were significantly associated with hemorrhagic bullae presentation, blood stream infection, and mortality. Physicians should be alert to NF patients with the appearance of bacteremia, shock, fever, higher WBC banded and segmented forms, and lower platelet counts at the emergency department, with patients revealed to more likely have Gram-negative infections. Ceftriaxone with/without other appropriate antibiotics under the supervision of infectious doctors appeared to be clinically effective for the treatment of NF and blood stream infections.